Lack of cyclin D-Cdk complexes in Rb-negative cells correlates with high levels of p16INK4/MTS1 tumour suppressor gene product. - Parry, D (1995)
D-type cyclins, in association with the cyclin-dependent kinases Cdk4 or Cdk6, regulate events in the G1 phase of the cell cycle and may contribute to the phosphorylation of the retinoblastoma gene product (Rb). However, in cells in which the function of Rb has been compromised, either by naturally arising mutations or through binding to proteins encoded by DNA tumour viruses, Cdk4 and Cdk6 are not associated with D cyclins. Instead, both kinases form binary complexes with a stable 16 kDa protein (p16) encoded by the putative tumour suppressor gene INK4/MTS1 on human chromosome 9p21. Here we show an inverse correlation between Rb status and the expression of p16. Since Rb-negative cells express high levels of p16, we suggest that in these cells p16 competes with D cyclins for binding to Cdk4 and Cdk6 and prevents formation of active complexes. In line with these predictions, DNA tumour virus oncoproteins do not disrupt cyclin D1-Cdk4 complexes in cells lacking p16.